2015
DOI: 10.1002/jor.22951
|View full text |Cite
|
Sign up to set email alerts
|

Compressive mechanical modulation alters the viability of growth plate chondrocytes in vitro

Abstract: The aim of this study was to investigate the effect of compressive modulation parameters (mode, magnitude, duration, as well as frequency and amplitude for cyclic modulation) on the viability of growth plate chondrocytes. Swine ulnar growth plate explants (n ¼ 60) were randomly distributed among 10 groups: baseline (n ¼ 1 Â 6); culture control (n ¼ 1 Â 6); static (n ¼ 3 Â 6); and dynamic (n ¼ 5 Â 6). Static and dynamic samples were modulated in vitro using a bioreactor. Different compression magnitudes (0.1 MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The hypertrophic chondrocytes are also more sensitive to compressive forces when compared with articular cartilage chondrocytes: they have decreased viability at lower mechanical loads. 25,26 It is already known that high impact loads on adult cartilage cause chondrocyte death, followed by cartilage matrix degradation and resulting chondronecrosis. 27 A recent in vitro impact injury study of bovine osteochondral cores of various cartilage thicknesses revealed that distinct injury patterns were observed with the degree of load.…”
Section: Discussionmentioning
confidence: 99%
“…The hypertrophic chondrocytes are also more sensitive to compressive forces when compared with articular cartilage chondrocytes: they have decreased viability at lower mechanical loads. 25,26 It is already known that high impact loads on adult cartilage cause chondrocyte death, followed by cartilage matrix degradation and resulting chondronecrosis. 27 A recent in vitro impact injury study of bovine osteochondral cores of various cartilage thicknesses revealed that distinct injury patterns were observed with the degree of load.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes respond differently depending on the frequency and amplitude and duration of loading. 157 Congdon et al revealed that articular cartilage and growth plate cartilage respond differently to mechanical stimuli. 158 Using AFM to compare the Young's modulus of the interterritorial matrix and PCM surrounding the chondrocytes showed that these elastic modulus values were greater for the interterritorial matrix, which has a more solid phase relative to those for the PCM with its more fluid phase.…”
Section: Mechanical Properties Of the Growth Plate Chondro-osseous Junctionmentioning
confidence: 99%
“…A 60.9 ± 3.4% decrease was reported in vitro in the ratio of expressions between the Bax and Bcl-2 (ratio = Bax/Bcl-2) genes under a 4000μ cyclic tensile strain, correlated to an increase in chondrocyte apoptosis. 7 Matrix metalloproteinase (MMP) mRNA, which encodes proteins involved in matrix degradation, has both remained stable in vivo under persistent 0.2 MPa static compression for two weeks in rat caudal vertebrae 36,39 34 altered expression in chicken tibiae when loaded with sandbags of 10% BW for up to 4 days. MMP-2, −9, and −13 upregulated while MMP-3 downregulated in this case.…”
Section: Chondrocyte Gene and Protein Expressionmentioning
confidence: 99%
“…Cell apoptosis, a form of cell death, was reported in vitro to increase with static tension applied for 6 h to human phalangeal growth plate chondrocytes. 7 Another in vitro study by Kaviani et al 34 indicated that cell viability was affected by load magnitude, duration, cyclic frequency, and amplitude. Chondrocytes were arrested at a magnitude of 0.2 MPa applied for 12 h whether static or cyclic, and by magnitude of 0.1 MPa when applied statically for 24 h to growth plate explants from 28-day-old pigs.…”
Section: Chondrocyte Count Height and Viabilitymentioning
confidence: 99%